Field effect studies on rubrene and impurities of rubrene - Zeis, Roswitha; Besnard, Celine; Siegrist, Theo; Schlockermann, Carl; Chi, Xiaoliu; Kloc, Christian (Chemistry of Materials, 2006)
Rubrene single crystals have been grown by a vapor-phase process. Two additional compounds that contaminate rubrene have been identified and their structures determined. Single crystals of rubrene show excellent crystallinity and very small rocking curve width. Field effect transistors based on pure rubrene single crystals with colloidal graphite electrodes and Parylene as a dielectric demonstrate a maximal mobility of 13 cm 2/Vs with strong anisotropy. The mobility increases very slightly with cooling, but decreases significantly at low temperatures. © 2006 American Chemical Society.
Created from Fastlane, Scopus look-up